Analysis of Methylation Dynamics Reveals a Tissue-Specific, Age-Dependent Decline in 5-Methylcytosine Within the Genome of the Vertebrate Aging Model Nothobranchius furzeri - Zupkovitz, Gordin; Kabiljo, Julijan; Kothmayer, Michael; Schlick, Katharina; Schöfer, Christian; Lagger, Sabine; Pusch, Oliver (Frontiers in Molecular Biosciences, 2021)
Erosion of the epigenetic DNA methylation landscape is a widely recognized hallmark of aging. Emerging advances in-high throughput sequencing techniques, in particular DNA methylation data analysis, have resulted in the establishment of precise human and murine age prediction tools. In vertebrates, methylation of cytosine at the C5 position of CpG dinucleotides is executed by DNA methyltransferases (DNMTs) whereas the process of enzymatic demethylation is highly dependent on the activity of the ten-eleven translocation methylcytosine dioxygenase (TET) family of enzymes. Here, we report the identification of the key players constituting the DNA methylation machinery in the short-lived teleost aging model Nothobranchius furzeri. We present a comprehensive spatio-temporal expression profile of the methylation-associated enzymes from embryogenesis into late adulthood, thereby covering the complete killifish life cycle. Data mining of the N. furzeri genome produced five dnmt gene family orthologues corresponding to the mammalian DNMTs (DNMT1, 2, 3A and 3B). Comparable to other teleost species, N. furzeri harbors multiple genomic copies of the de novo DNA methylation subfamily. A related search for the DNMT1 recruitment factor UHRF1 and TET family members resulted in the identification of N. furzeri uhrf1, tet1, tet2 and tet3. Phylogenetic analysis revealed high cross-species similarity on the amino acid level of all individual dnmts, tets and uhrf1, emphasizing a high degree of functional conservation. During early killifish development all analyzed dnmts and tets showed a similar expression profile characterized by a strong increase in transcript levels after fertilization, peaking either at embryonic day 6 or at the black eye stage of embryonic development. In adult N. furzeri, DNA methylation regulating enzymes showed a ubiquitous tissue distribution. Specifically, we observed an age-dependent downregulation of dnmts, and to some extent uhrf1, which correlated with a significant decrease in global DNA methylation levels in the aging killifish liver and muscle. The age-dependent DNA methylation profile and spatio-temporal expression characteristics of its enzymatic machinery reported here may serve as an essential platform for the identification of an epigenetic aging clock in the new vertebrate model system N. furzeri.